Konseling Melalui Meditasi Lintas Agama di Vihara Karangdjati Yogyakarta - Ubudiyah, Farikhatul (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Neuroscience finds a function of the nervous system that affects the actions of an individual. Neuroscience influences spiritual and religious experience. The calm balance of nerves and waves will reach a point of calm to God Spot. Meditation can be used as a medium in that direction. This article describes meditation in the view of neuroscience can affect spiritual and religious experience of a person. This qualitative field research took data from the Karangdjati monastery in Yogyakarta, focusing on meditation activities. Meditation there is not only for Buddhism, but its followers come from various adherents of formal religions. What they do can be seen as cross-cultural and religious counseling. Relying on mind and spiritual strength, meditation affects behavior and reduces feelings of stress or other illnesses. The discovery of the meaning and resolution of the problems of the mediation actors can be achieved through spiritual practice and their religious experience and socialization between members after the activity.